A Novel Technique for Particle Sizing by Image Analysis of the Diffraction Pattern - R. Salah; Muzalhim Ibrahim Azawe (Institut Teknologi Bandung, 2011)
We analyze the image of an aggregate of particles based on laser diffraction technique for particle diameter calculations. The recorded image will be transferred to a matrix of pixels, depending on the size of the image, and these pixels will be correlated with each other and with surroundings in order to get the exact features of the image. Processing of the image through many steps in the software will allow finding the diameter. The diameter obtained by this technique will be compared with the diameter found from the image of the optical microscope.